BENTUK PENYAJIAN LAGU OEMAR BAKRIE DI MARCHING BAND SWATAMI PADA GEBYAR PENDIDIKAN NASIONAL KABUPATEN LABUHANBATU UTARA - Buana, Utari Arsy (Grenek: Jurnal Seni Musik, 2018)
The results showed that one form of emotional expression that is channeledthrough the music and therefore, the group marching band Swatami onarranemen songs Oemar Bakrie brought by Marching band Swatami using threecategories of instrument, namely: instrument Percussion in tone (Glockenspiel,vibraphone, Xylophone, Marimba), brass instruments (trumpet, Mellophone,Baritone, Tuba), and percussion (Senar drum, tenor drum, bass drum, cymbals).Choosing songs Omar bakrie for in the arrangements with the shape Marchingband. Bakrie Oemar tempo songs using 163 has 51 bars and has two variations ofthe melody, the melody forms A and B. Form benuk melodic presentation of thesong sung by Oemar Bakrie Swatami Marching band is a form of selfappreciation for issuing arts talent. Using costumes and makeup of their pridethat seemed interesting and luxurious for a show. Using display / position playersmake this show the higher thevalue of his art.